A Local Community Course That Raises Wellbeing and Pro-sociality: Evidence from a Randomised Controlled Trial - Christian Krekel; Jan-Emmanuel De Neve; Daisy Fancourt; Richard Layard (Institute of Labor Economics (IZA), 2021)
Despite a wealth of research on its correlates, relatively little is known about how to effectively raise wellbeing in local communities by means of intervention. Can we teach people to live happier lives, cost-effectively and at scale? We conducted a randomised controlled trial of a scalable social-psychological intervention rooted in self-determination theory and aimed at raising the wellbeing and pro-sociality of the general adult population. The manualised course ("Exploring What Matters") is run by non-expert volunteers (laypeople) in their local communities and to date has been conducted in more than 26 countries around the world. We found that it has strong, positive causal effects on participants' subjective wellbeing and pro-sociality (compassion and social trust) while lowering measures of mental ill health. The impacts of the course are sustained for at least two months post-treatment. We compare treatment to other wellbeing interventions and discuss limitations and implications for intervention design, as well as implications for the use of wellbeing as an outcome for public policy more generally.
Keywords: C93; I12; I31; 330; wellbeing; pro-social behaviour; communities; intervention; RCT